2018
DOI: 10.1111/sms.13081
|View full text |Cite
|
Sign up to set email alerts
|

Football training improves metabolic and cardiovascular health status in 55‐ to 70‐year‐old women and men with prediabetes

Abstract: We examined the effects of 16 weeks of football training and dietary advice on blood glucose control and health status in 55‐ to 70‐year‐old women and men with prediabetes. Fifty participants with prediabetes (age; 61 ± 6 years, BMI; 29.6 ± 4.7; VO2max 22.3 ± 5.7 mL·min−1·kg−1) were randomized into a football and dietary advice group (F+D; n = 27) and a dietary advice group (D; n = 23). F+D performed football training (twice weekly 30‐ to 60‐minutes sessions) and received dietary advice, while D only received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Additionally, RF was associated (in middle‐age and older people) with decreased cholesterol and triglycerides levels, plasma glucose and IGFBP‐3 levels (contributing to higher insulin sensitivity), decreased ammoniagenesis, and increased lipolytic activity and IGF‐1/IGFBP‐3 ratio, all indicative of attenuated catabolism . More recently, Skoradal et al also demonstrated that a program of 16 weeks of football training and dietary advice has positive effects on metabolic and cardiovascular health profiles, with greater overall effects than professional dietary advice per se for 55‐ to 70‐year‐old women and men with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RF was associated (in middle‐age and older people) with decreased cholesterol and triglycerides levels, plasma glucose and IGFBP‐3 levels (contributing to higher insulin sensitivity), decreased ammoniagenesis, and increased lipolytic activity and IGF‐1/IGFBP‐3 ratio, all indicative of attenuated catabolism . More recently, Skoradal et al also demonstrated that a program of 16 weeks of football training and dietary advice has positive effects on metabolic and cardiovascular health profiles, with greater overall effects than professional dietary advice per se for 55‐ to 70‐year‐old women and men with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…12 weeks of recreational football training (3 × 40 min/week), combined with a calorie-restricted diet, improves metabolic and CV fitness both in middle-aged and in older diabetic subjects, compared to diet group [66]. These positive results are evidenced in another randomized controlled study in which middle-aged and older pre-diabetic subjects performed a 16 weeks intervention (Football training twice weekly 30to 60-min/sessions + Dietary advice, F + D) confirming a greater improvement in metabolic and CV health profile in F + D group compared to Dietary advice group (D) [75].…”
Section: Football and Healthmentioning
confidence: 83%
“…Moreover, the plasma D-vitamin levels ranged between 55 and 65 nmol/L during the intervention (see Ref. [27]), which is below the recommendations of 75-150 nmol/L for patients with deteriorated bone quality. In addition, several participants displayed levels <50 (~40%) and <75 nmol/L (~75%) (data not shown) during the experimental period.…”
Section: Discussionmentioning
confidence: 93%
“…Plasma D-vitamin did, however, not differ between groups or pre-and post-measurements. 27 Peak bone mass is attained in both genders in the second decade of life, but a decrease of approximately 1% annually occurs midlife and onwards with an accelerated decrease in women during the first few years after menopause. 29 Thus, the ~2% increase in leg bone mineral density and ~3% increase in bone mineral content in the present study in only 16 weeks underlines that the osteogenic effects were significant.…”
Section: Discussionmentioning
confidence: 99%